2016
DOI: 10.1523/jneurosci.2480-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Modal Attention Effects in the Vestibular Cortex during Attentive Tracking of Moving Objects

Abstract: The midposterior fundus of the Sylvian fissure in the human brain is central to the cortical processing of vestibular cues. At least two vestibular areas are located at this site: the parietoinsular vestibular cortex (PIVC) and the posterior insular cortex (PIC). It is now well established that activity in sensory systems is subject to cross-modal attention effects. Attending to a stimulus in one sensory modality enhances activity in the corresponding cortical sensory system, but simultaneously suppresses acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 40 publications
(1 reference statement)
6
40
0
Order By: Relevance
“…Area PIC in the Sylvian fissure is a motion region responding to visual and vestibular motion, presumably supporting the integration of motion information from visual and vestibular senses for the perception of self-motion (Frank, Sun, et al, 2016;Frank, Wirth, & Greenlee, 2016). A recent study by Huang et al (2015) found that the right PIC (there called PIVC) responds to active dodges suggesting that it plays an active role in sensing and guiding translational egomotion.…”
Section: Cortical Areas Preferring Onboard Movies (Inducing Self-momentioning
confidence: 85%
See 3 more Smart Citations
“…Area PIC in the Sylvian fissure is a motion region responding to visual and vestibular motion, presumably supporting the integration of motion information from visual and vestibular senses for the perception of self-motion (Frank, Sun, et al, 2016;Frank, Wirth, & Greenlee, 2016). A recent study by Huang et al (2015) found that the right PIC (there called PIVC) responds to active dodges suggesting that it plays an active role in sensing and guiding translational egomotion.…”
Section: Cortical Areas Preferring Onboard Movies (Inducing Self-momentioning
confidence: 85%
“…, Amunts,Mohlberg, & Zilles, 2006;Fasold et al, 2002;Friberg, Olsen, Roland, Paulson, & Lassen, 1985;Indovina et al, 2005), or visual stimuli(Cardin & Smith, 2010). Thus, previously reported activations in posterior lateral sulcus during self-motion induced by visual motion(Cardin & Smith, 2010;Huang et al, 2015;Uesaki & Ashida, 2015) might fall within PIC, or at least partially overlap with PIC, rather than PIVCFrank, Sun, et al, 2016;Frank, Wirth, & Greenlee, 2016;Greenlee et al, 2016). PIVC is located more anteriorly, in correspondence of the lateral end of the central sulcus.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…However, it is not clear whether the vestibular cortical core region is a single area. Frank and colleagues, based on recent function and structural brain imaging studies (Billington & Smith, ; Frank & Greenlee, ; Frank, Sun, Forster, Tse, & Greenlee, ; Frank, Wirth, & Greenlee, ; Schindler & Bartels, ; Wirth, Frank, Greenlee, & Beer, ), have found some evidence for the existence of at least one other; this region has been named the posterior insular cortex area (PIC). The PIC is located in the retroinsular cortex posterior to the PIVC (Frank, Wirth, et al, ).…”
Section: Discussionmentioning
confidence: 99%